An analysis of a social sciences curriculum from the perspective of critical peace education - Kuter, Sitkiye; Sanal-Erginel, Senem (Routledge Journals, Taylor & Francis Ltd, 2025)
This study focuses on critical peace education in a post-conflict context in Northern Cyprus. It aimed to analyse the Social Sciences curriculum (year group 7) using a framework that was developed as part of the present study benefitting from the literature on critical peace education. The study employed an interpretive critical inquiry method for document analysis within the qualitative research paradigm. The findings indicated that the learning objectives in the Social Sciences curriculum targeted knowledge and moral capacity building with an individualistic focus and with local, historical, and globalised orientation. Numerous recommendations were made for the improvement of the curriculum, based on the principles and orientations of critical peace education.
Keywords: Critical peace education; critical pedagogy; social sciences curriculum; curriculum analysis; post-conflict country